Animal Welfare and the United Nations Sustainable Development Goals - Keeling, Linda; Tunón, Håkan; Olmos Antillón, Gabriela; Berg, Charlotte; Jones, Mike; Stuardo, Leopoldo; Swanson, Janice; Wallenbeck, Anna; Winckler, Christoph; Blokhuis, Harry (Frontiers in Veterinary Science, 2019)
This paper systematically evaluates the extent to which achieving the UN sustainable development goals (SDGs) is compatible with improving animal welfare. The analyses were based on discussion and independent scoring in a group of 12 participants with academic backgrounds within agricultural or veterinary sciences. We considered all categories of animals; those kept for food production, working and companion animals, but also laboratory and wild animals. The strengths of the links between improving animal welfare and achieving an SDG were scored on a 7-point scale, from being completely indivisible, at one end of the scale, to where it is impossible to reach both the SDG and improved animal welfare at the same time. There was good consensus between participants, with the overall scores being positive, indicating that although animal welfare is not explicitly mentioned in the SDGs, working to achieving the SDGs is compatible with working to improve animal welfare. When analysing the direction of the links, the impact of achieving an SDG was considered, on average, to be slightly better at leading to improved animal welfare, than the impact of improving animal welfare was on achieving the SDG. The exception to this was for SDG 2, dealing with zero hunger. The two SDGs for which there was strongest mutual reinforcing were SDG 12, which deals with responsible production and consumption, and SDG 14, which deals with life below water. Most of the targets under these two SDGs were considered relevant to animal welfare, whereas when all SDGs were considered, 66 targets of the total of 169 were considered relevant. Although the results of this study suggest a mutually beneficial relationship between improving animal welfare and achieving SDGs, this should be confirmed on a wider group of people, for example people from less developed countries and other stakeholders. Showing the relationships between animal welfare and the sustainable development goals helps highlight the importance of animal welfare when implementing these goals in practice. The methodology described in this study could also be useful to researchers working with other societal and environmental issues not yet considered within the overall SDG framework